Analisis Unjuk Kerja Perubahan Jumlah Node dan RAW Station pada IEEE 802.11ah - Triani Wulandari; Doan Perdana; Ridha Muldina Negara (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
Rapid development of wireless network impacts the development of IEEE 802.11x standard technology. However, the existing standard technologies still can not solve the problem of capacity, coverage, and power consumption. Due to these limitations, IEEE 802.11ah standard was made. IEEE 802.11ah is a standard of Wi-Fi technology that supports wireless networking scenarios, such as ability to arrange the large number of devices, a wide range of coverage, and power consumption mechanism on a limited energy condition. Wireless network is a best-effort network in delivering package. But VoIP service on the wireless network has lower QoS value, compared to the network using cables. This paper addresses the performance analysis of 802.11ah standard against VoIP services, especially at the MAC layer. To analyze the influence of node density and performance of RAW mechanism on VoIP service, a simulation is conducted through two scenarios, which are changing the number of nodes and RAW station. The simulation is performed using network simulator NS3 version 3.23. Analysis results show with the increasing number of nodes, the value of throughput and delay increase by 60.09% and 93.43%. Then, with the increasing number of RAW station, throughput and delay value have increased by 81.54% and 43.45%. The increase stops in a constant value when the number of RAW station has exceeded the number of nodes in the network.